2011
DOI: 10.1007/s00383-011-2988-z
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis sensitizers enhance cytotoxicity in hepatoblastoma cells

Abstract: The data provide evidence that ABT-737 and obatoclax might improve treatment results in children with HB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Western blot analysis was performed as previously described [24]. For detection of histone H3 phosphorylation rabbit anti-phospho-Histone H3 (Ser 10) antibody was used.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Western blot analysis was performed as previously described [24]. For detection of histone H3 phosphorylation rabbit anti-phospho-Histone H3 (Ser 10) antibody was used.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…All three Bcl-2 SMIs currently in clinical trials have shown to potentiate and synergize with chemotherapy and radiation in vitro 22 , 64 - 72 . Interestingly, mitogen-activated protein kinase (MAPK) pathway inhibitors, such as the epidermal growth factor receptor (EGFR) inhibitor gefitinib and erlotinib or the MEK inhibitor UO126 synergize with Bcl-2 SMIs 73 - 76 .…”
Section: Clinical Relevance Of Bcl-2 Inhibitorsmentioning
confidence: 99%
“…The repertoire of BCL-2 family proteins appears to change in cells grown as spheroids, compared to the same cell line grown as a monolayer. Increases in the expression of BCL-2 and BCL-X L have been observed in spheroids [108-111], and decreases in the expression of MCL-1 has also been reported [108,109]. This implies a switch towards an ABT-737-sensitive phenotype in cells grown as spheroids.…”
Section: Factors That Complicate Measurement Of Sensitivity To Bh3 MImentioning
confidence: 99%
“…This implies a switch towards an ABT-737-sensitive phenotype in cells grown as spheroids. Thus, even though increased resistance to either cisplatin or the combination of bortezomib and TRAIL was observed when cells were grown as spheroids, this could be overcome by exposure to ABT-737 [108,109]. The expression of pro-apoptotic family members may also be changed, and the growth of melanoma cells in spheroids leads to reduced expression of NOXA [26] but increased expression of BIM confers sensitivity to ABT-737 [112].…”
Section: Factors That Complicate Measurement Of Sensitivity To Bh3 MImentioning
confidence: 99%